Development of Interactive E-modules Using Problem Based Learning Model the Independent Curriculum to Entrance High School Student Critical Thingking Skils - Apriani, Yelsi; Medriati, Rosane; Setiawan, Iwan (Kasuari: Physics Education Journal (KPEJ), 2025)
This research focuses on evaluating the feasibility, student responses, and the enhancement of critical thinking skills among high school learners through the use of a Problem-Based Learning (PBL) interactive e-module centered on heat and thermodynamics. Utilizing the Research and Development (R&D) approach through the ADDIE framework, which comprises five distinct phases: analysis, design, development, implementation, and evaluation, the study employed various instruments like observations, interviews, questionnaires, and assessments of critical thinking skills. The findings indicated that the interactive e-module is highly feasible, achieving a score of 87.96%. Student feedback regarding the e-module was also overwhelmingly positive at 82.24%. Furthermore, the assessment of critical thinking enhancements indicated a significant improvement, with an N-Gain of 0.71 categorized as high when comparing pretest and posttes scores. In summary, the interactive e-module developed under the PBL framework is not only appropriate for testing but also significantly boosts students' critical thinking abilities.